Pengaruh Stres Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada Divisi Procurement and Fixed Assets (PFA) Di PT Bank Negara Indonesia (Persero) Tbk Cabang Tangerang Selatan - Dewi, Vika Tresna (Jurnal ATAMA, 2023)
The purpose of this study was to determine the effect of work stress on employee performance, the impact of the work environment on employee performance, and the effect of work stress and the work environment together on employee performance at PT. Bank Negara Indonesia (Persero) Tbk. South Tangerang Branch. This research uses quantitative methods by using descriptive and verification analysis. The descriptive method is used by collecting and analyzing data. The population in this study is 100 employees, while the sample for this study is 100 samples using a saturated selection. The results of this study are partially or simultaneously that work stress and work environment significantly affect employee performance. More than that, the contribution of these two variables produces 71.5% in influencing employee performance.